An Insight into the Cosmetic and Dermatologic Applications of the Molecules of Palmyra Palm - Sunehra Sayanhika; Paulraj Mosae Selvakumar (Cosmetics, 2024)
Palmyra palm is a resourceful plant species that can be put to use in superabundance. Its extensive range of use stretches in all directions—making it useful for consumption in countless forms, and the cosmetic industry is not a deviation from this. In accordance with the beneficial molecules generated in it, such as polyphenols, flavonoids, carotenoids and others, the addition of Palmyra raises incentives like reduction and microbe prevention when developed into therapeutic products. Therefore, the virtues of Palmyra fruit, sap, leaves, pulp, bark, haustoria and other parts are being diversely exploited in the beauty and health industry at present. To summarise the compass of Palmyra palm and its products in cosmetology and dermatology, an overview is drafted exploring the extant literature on the topic. Following the description of the available molecules, their adoption into skincare products and in vivo effects was analysed in this study. Aiming to highlight the prospects of Palmyra in skin and personal care formulations, this article discusses the span of its potential in light of its physicochemical attributes.